Optimal Decisions for a Fuzzy Two-Echelon Supply Chain - Qingfeng Song; Kai Shi; Sheng Lin; Guangping Xu (Discrete Dynamics in Nature and Society)
This paper discusses the optimal decisions of pricing and selling effort for a two-echelon supply chain with uncertain consumer demands, manufacturing costs, and selling costs. In order to maximize the α-optimistic value of the profits, based on different market structures, one centralized decision model and three decentralized decision models are developed, and the corresponding analytical equilibrium solutions are obtained using the game-theoretical approach. The results illustrate that no matter what decision case is, the optimal retail and wholesale prices in the case of considering selling effort are, respectively, larger than those of no selling effort; the optimal profits of the manufacturer, the retailer, and the whole supply chain system in the case of considering selling effort are, respectively, larger than those of no selling effort except for the profit of the retailer in the case that the manufacturer plays the leader’s role. Finally, one numerical example is presented, which illustrates the effectiveness of the proposed models.